Management of Strategic Changes in Enterprises under Conditions of European Integration - Lina Artemenko; Ліна Артеменко; Maryna Pereskoka; Марина Перескока; Pereszkoka M. (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. The purpose of this study is to examine the process of managing strategic changes in enterprises in the context of European integration, with a particularemphasis on potentialchallenges andadaptation strategies to European standards. Underthe current conditions of European integration, enterprises are required to adjustto new regulationsset by the EU, which requires rapid and effective transformationsin management strategies and organizational processes.The research methodology involvesa theoretical analysis of the keymodels of change management, such as the models of John Kotter and Kurt Lewin, as well as practical cases of change implementation in Ukrainian enterprises that are integrating into the EU economic space. The analysis of these casesmade it possible to identifythe main success factors in the process of implementing change, among which effective leadership, corporate culture, innovation capacity, and continuous monitoringand evaluation of results play a crucialrole. The results of the study show that enterprises that actively use change management strategies and integrate European standards are able to adapt successfully to new conditions, in particular through the modernization of production facilities, the introduction of new technologies, the improvement of staff qualifications, and the implementation of new business models. The study of practical examples also confirms the importance of developing tailored strategies for different stages of the European integration process.The practical significance of the research results lies in the fact that the proposed approaches can be applied by enterprises to improve management processes, increase the effectiveness of adaptation to change, and strengthen their competitiveness in international markets. This will allow enterprises to significantly reduce the risks associated with integration into European markets, as well as lowerthe costs of modernizing production. The recommendations presentedin the study are universal in nature and can be used by enterprises in various industries to improve the effectiveness of change management in the context of globalization and European integration.The study's findings also confirm the need to integrate innovative approaches into enterprise management strategies to ensure their sustainability and adaptability in a constantly changing economic environment.

A kutatás célja a stratégiai változások irányításának vizsgálata a vállalatoknál az európai integráció feltételei között, különös tekintettel a lehetséges kihívásokra és az európai szabványokhoz való alkalmazkodási stratégiákra. A mai európai integráció körülményei között a vállalkozásoknak alkalmazkodniuk kell az EU új követelményeihez, ami gyors és hatékony változásokat igényel a vezetési stratégiákban és a szervezeti folyamatokban.A kutatás módszertana magában foglalja a változások kezelésének főbb modelljeinek, például John Kotter és Kurt Lewin modelljeinek elméleti elemzését, valamint gyakorlati eseteket a változások bevezetéséről az EU gazdasági térségébe integrálódó ukrán vállalatoknál. Ezeknek az eseteknek az elemzésével azonosították a változások bevezetésének folyamatában a siker fő tényezőit, amelyek között kiemelt szerepet játszanak a hatékony vezetés, a vállalati kultúra, az innovációs képesség, valamint az eredmények folyamatos nyomon követése és értékelése.A kutatás eredményei azt mutatják, hogy azok a vállalkozások, amelyek aktívan alkalmazzák a változáskezelési stratégiákat és integrálják az európai szabványokat, képesek sikeresen alkalmazkodni az új feltételekhez, különösen a termelési kapacitások modernizálása, új technológiák bevezetése,a személyzet továbbképzése és új üzleti modellek bevezetése révén. A gyakorlati példák tanulmányozása szintén megerősíti az európai integrációs folyamat különböző szakaszaihoz igazított stratégiák kidolgozásának fontosságát.A kutatás eredményeinek gyakorlati jelentősége abban rejlik, hogy a javasolt megközelítéseket a vállalkozások alkalmazhatják a menedzsment folyamatok javítására, a változásokhoz való alkalmazkodás hatékonyságának növelésére, valamint versenyképességük erősítésére a nemzetközi piacokon.Ez lehetővé teszi a vállalkozások számára, hogy jelentősen csökkentsék az európai piacokba való integrációval kapcsolatos kockázatokat, valamint csökkentsék a termelés modernizálásának költségeit. A tanulmányban szereplő ajánlások univerzális jellegűek, és különböző iparágak vállalkozásai felhasználhatják őket a globalizáció és az európai integráció feltételei között a változások kezelésének hatékonyságának növelésére. A tanulmány következtetései megerősítik annak szükségességét is, hogy az innovatív megközelítéseket integrálják a vállalkozások irányítási stratégiáiba, hogy biztosítsák azok fenntarthatóságát és alkalmazkodóképességét a folyamatosan változó gazdasági környezetben.

Резюме. Метою даного дослідження є вивчення процесу управління стратегічними змінами на підприємствах в умовах євроінтеграції, з акцентом на можливі виклики та адаптаційні стратегії до європейських стандартів. У сучасних умовах євроінтеграції підприємства стикаються з необхідністю адаптації до нових вимог, що висуваються ЄС, що вимагає швидких і ефективних змін в управлінських стратегія та організаційних процесах.Методика дослідження включає теоретичний аналіз основних моделей управління змінами, таких як моделі Джона Коттера та Курта Левіна, а також практичні кейси впровадження змін на підприємствах України, що інтегруються в економічний простір ЄС. За допомогою аналізу цих кейсів було виявлено основні фактори успіху в процесі впровадження змін, серед яких особливу роль відіграють ефективне лідерство, корпоративна культура, здатність до інновацій, а також постійний моніторинг і оцінка результатів.Результати дослідження показують, що підприємства, які активно використовують стратегії управління змінами таінтегрують європейські стандарти, здатні успішно адаптуватися до нових умов, зокрема через модернізацію виробничих потужностей, впровадження нових технологій, підвищення кваліфікації персоналу та впровадження нових бізнес-моделей. Вивчення практичних прикладів також підтверджує важливість розробки адаптованих стратегій для різних етапів євроінтеграційного процесу.Практична значущість результатів дослідження полягає в тому, що запропоновані підходи можуть бути застосовані підприємствами для покращення управлінських процесів, підвищення ефективності адаптації до змін, а також для посилення їх конкурентоспроможності на міжнародних ринках. Це дозволить підприємствам значно знизити ризики, пов’язані з інтеграцією до європейських ринків, а також скоротити витрати на модернізацію виробництва. Рекомендації, викладені в дослідженні, мають універсальний характер і можуть бути використані підприємствами різних галузей для підвищення ефективності управління змінами в умовах глобалізації та євроінтеграції.Висновки дослідження також підтверджують необхідність інтеграції інноваційних підходів в управлінські стратегії підприємств для забезпечення їх стійкості та адаптивності в умовах постійно змінюваного економічного середовища.
Управління стратегічними змінами на підприємстві в умовах євроінтеграції
A stratégiai változások irányítása a vállalkozásban az európai integráció feltételei között
Весь випуск: https://aab-economics.kmf.uz.ua/aabe/issue/view/11
Keywords: change management; European integration; strategic management; adaptation to European standards; competitiveness